Side Effects of Clozapine Treatment in Patients with Schizophrenia and Schizoaffective Disorder and Their Role in the Discontinuation of Treatment - Rümeysa Taşdelen; Hatice Kaya; Alp Üçok (Boğaziçi Tıp Dergisi, 2023)
INTRODUCTION: Clozapine is an effective atypical antipsychotic that has been successfully used in the treatment of schizophrenia and schizoaffective disorder, but its utilization is restricted due to the side effects. We aimed to investigate the side effects reported by patients using clozapine and their role in the cessation of the treatment. METHODS: In our study, the follow-up charts and admission files of patients with schizophrenia and schizoaffective disorder who were followed up regularly at outpatient clinics were reviewed retrospectively. 246 patients who had received or are currently taking clozapine were identified. The sociodemographic and clinical features of the patients, reported side effects, and the reasons for discontinuation were recorded. RESULTS: The most frequently side effects reported by the patients were sedation (35.6%), hypersalivation (27.9%), weight gain (19%), incontinence (8.1%), obsessive–compulsive symptoms (6.5%), seizure-myoclonus (4.9%), orthostatic hypotension (4.5%), leukopenia (3.6%), sexual side effects (1.2%), and constipation (0.8%). Clozapine treatment was terminated in 26.6% of the patients due to non-adherence to medication (35.4%), inadequate effect/side effect ratio (13.8%), ineffectiveness (12.3%) leukopenia (9.2%), seizures (7.7%), incontinence (6.2%), sedation (6.2%), obsessive–compulsive symptoms (3.1%), weight gain (3.1%), hypersalivation (1.5%), and orthostatic hypotension (1.5%). When the reasons for discontinuation were analyzed, it was determined that failure to provide sufficient effect and irregular use were significantly higher in patients who have a history of more suicide attempts. DISCUSSION AND CONCLUSION: Side effects of clozapine treatment are common. Approximately one-quarter of patients receiving clozapine discontinued the treatment due to intolerance of side effects, non-adherence to treatment, or failure to provide sufficient effect. In patients with a worse course since the onset of the disease, treatment discontinuation due to insufficient efficacy and irregular use was higher.